2019
DOI: 10.3390/ijms20133335
|View full text |Cite
|
Sign up to set email alerts
|

PEA-15 C-Terminal Tail Allosterically Modulates Death-Effector Domain Conformation and Facilitates Protein–Protein Interactions

Abstract: Phosphoprotein enriched in astrocytes, 15 kDa (PEA-15) exerts its regulatory roles on several critical cellular pathways through protein–protein interactions depending on its phosphorylation states. It can either inhibit the extracellular signal-regulated kinase (ERK) activities when it is dephosphorylated or block the assembly of death-inducing signaling complex (DISC) and the subsequent activation of apoptotic initiator, caspase-8, when it is phosphorylated. Due to the important roles of PEA-15 in regulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 37 publications
7
6
0
Order By: Relevance
“…When it comes to bind with FADD, little conformational change is needed to form the complex. This simulated PEA-15pp/FADD model agrees well with our initial NMR assessment on the complex, which demonstrated that the phosphorylation of PEA-15 C-terminal serine residues signi cantly modulate DED conformation, while binding to FADD does not seem to induce additional conformational change of PEA-15pp 17 . In an effort to partially assign the NMR spectra of PEA-15 S104D/S116D double mutant (PEA-15DD), mimicking the doubly phosphorylated state and having similar in vivo effects and binding speci city to FADD 25 , we identify that the residues experiencing the most chemical shift perturbations between the free PEA-15DD and the FADD-bound form are mostly located on helices α5 and α6, including Arg-71, which engages in direct interactions with FADD.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…When it comes to bind with FADD, little conformational change is needed to form the complex. This simulated PEA-15pp/FADD model agrees well with our initial NMR assessment on the complex, which demonstrated that the phosphorylation of PEA-15 C-terminal serine residues signi cantly modulate DED conformation, while binding to FADD does not seem to induce additional conformational change of PEA-15pp 17 . In an effort to partially assign the NMR spectra of PEA-15 S104D/S116D double mutant (PEA-15DD), mimicking the doubly phosphorylated state and having similar in vivo effects and binding speci city to FADD 25 , we identify that the residues experiencing the most chemical shift perturbations between the free PEA-15DD and the FADD-bound form are mostly located on helices α5 and α6, including Arg-71, which engages in direct interactions with FADD.…”
Section: Discussionsupporting
confidence: 81%
“…The backbone RMSD for PEA-15pp DED (before the kink) is only 0.803 Å between the free and FADD-bound structures. The simulation results of PEA-15pp in its free and FADD-bound form are consistent with our earlier NMR data, which indicated that phosphorylation at S104 and S116, mimicked by serine to aspartic acid mutation, on the C-terminal tail stimulates a conformational change at the DED, and FADD binding does not induce additional changes in DED conformation 17 . The NMR data and the current MD simulations both suggest that phosphorylation of C-terminal serine residues is enough to modulate the DED structure, converting the protein conformation better suited to bind with FADD.…”
Section: Complex Structure Of Unphosphorylated Pea-15 With Erk2supporting
confidence: 89%
See 1 more Smart Citation
“…This difference is primarily associated with the phosphorylation status of PED/PEA-15; in ovarian cancer, PED/PEA-15 is unphosphorylated ( 31 ). Therefore, PED/PEA-15 acts either as a tumor promoter or as a tumor suppressor, modulating cell proliferation or apoptosis depending on its phosphorylation status ( 11 ). Phosphorylated PED/PEA-15 is associated with increased ERK1/2 activity compared with that in non-tumorous cells, leading to increased cell growth and migration and, consequently, tumor promotion ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PED/PEA-15 regulates a range of cellular processes, including cell proliferation, apoptosis and migration in numerous types of cancer, such as breast and lung cancer ( 9 , 10 ). Notably, PED/PEA-15 acts as a tumor-promotor or a tumor-suppressor depending on its phosphorylation status ( 11 ). The unphosphorylated form binds extracellular signal receptor-activated kinase 1/2 (ERK1/2), suppressing its subsequent activation; by contrast, phosphorylation of PED/PEA-15 at Ser116 [PED/PEA-15(S116)] releases ERK1/2, resulting in its activation, which causes cell proliferation and migration, and thus, tumor promotion, including lung, breast and prostate cancer ( 9 , 10 , 12 ).…”
Section: Introductionmentioning
confidence: 99%